Description of a new leafhopper species of the genus Watanabella (Hemiptera, Cicadellidae, Deltocephalinae) from China - Zhang, Lan; Xing, Jichun (Zootaxa, 2020)
A new leafhopper species Watanabella curvatua sp. nov., is described and illustrated from Yunnan Province, China. New synonyms are revealed, Paramacrosteles Dai, Li & Chen, 2006 is a junior synonym of Watanabella Vilbaste, 1969 and Paramacrosteles nigromaculatus Dai, Li & Chen, 2006 is a junior synonym of Watanabella graminea Choe, 1981. A key is given to distinguish all species of the genus. The type specimen of the new species is deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).